Integrating STEAM in Project-Based Learning to Foster Soft Skills in Higher Education - Maulina, Julia; Dewi, Sinta Verawati; Zuhri; Zakiah, Nina; Happy, Nurina; Rafiqoh, Sri (Mimbar Ilmu, 2024)
Soft skills are essential factors in preparing students to face the increasingly competitive job market. However, traditional learning methods often pay less attention to the development of these non-technical skills. This study aims to analyze the impact of project-based learning integrated with STEAM (Science, Technology, Engineering, Arts, and Mathematics) on improving students' soft skills in the Organic Chemistry course, particularly in the topic of hydrocarbons. The research employs a quantitative approach with a descriptive-correlational design. The sample was selected purposively, involving 33 students who took the Organic Chemistry. Data were collected through a closed-ended questionnaire using Google Form, and the data analysis was conducted using simple linear regression. The results showed that the project-based learning method integrated with STEAM (PJBL-STEAM) had a significant impact on the development of students' soft skills, with a determination coefficient (R²) value of 0.300. This indicates that the method explains 30% of the variation in soft skills improvement, while the remaining percentage is influenced by other factors beyond this study. In conclusion, this study highlights that PJBL-STEAM is not only effective in enhancing students' technical abilities but also plays a crucial role in developing the non-technical skills required in professional settings.